Factors That Influence The Interest Of Accounting Study Program Students In Choosing A Career As An Educator Accountant Profession For Students Of Private Universities In Palembang City - Ferianti, Novi; Pandriadi, Pandriadi; Hadli, Hadli (Universitas Dehasen Bengkulu, 2024)
This study is a quantitative research. It aims to identify the factors that influence the interest of accounting students in choosing a career as an accounting educator among undergraduate accounting students at private universities in the city of Palembang. This research adopts motivation theory and expectancy theory. The method used in this study is quantitative. The type of data used is primary data, collected through questionnaires distributed to accounting students at private universities in Palembang who were actively enrolled in the 6th and 8th semesters during the 2021/2022 and 2022/2023 academic years. The population of this study consists of 1,102 students, and the sample was determined using the Isaac and Michael formula with a purposive sampling method. A total of 217 respondents were obtained, consisting of students from the Faculty of Economics and the Accounting Study Program at private universities in Palembang. This study uses statistical analysis tools. Based on the t-test results, the significance values are as follows: financial rewards (0.666 > 0.05), professional recognition (0.002 < 0.05), work environment (0.274 > 0.05), and job opportunities (0.000 < 0.05). The results indicate that financial rewards have no significant influence on the choice of a career as an accounting educator, while professional recognition has a significant influence. Similarly, the work environment does not significantly affect the choice of becoming an accounting educator, whereas job opportunities have a significant effect.